Online education for high intellectual ability students: An assessment of a mathematical program - Javier Tourón; Guillermina Marcos; Marta Tourón (Revista Electrónica Interuniversitaria de Formación del Profesorado)
In this paper a Mathematics multimedia interactive online program is evaluated. It was used by 215 ten-year old students with a verbal or quantitative capacity which situated them in the top 10% of their age group. The program lasted twelve weeks from March to May 2009. The students’ evaluation of the experience was very positive: 82% would repeat the experience and 94% would recommend it to class mates. Also the average evaluation of the program on a five point Likert scale was 4,17, that of the virtual classroom 3,94, and that of the tutor 4,58. The student learning evaluation indicates significant improvements between the pretest and the posttest, with values between 5 and 20 points. A few considerations are made on the possibilities of on-line learning to be adjusted to the educational needs of all students.